Method of operative determination of the stability of circulating water with regard to the release of CaCO3 - Kochmarskii, V Z; Moshynskyi, V S (IOP conference series. Earth and environmental science, 2023)
Sediments on the technological surfaces of the recirculating water supply system (RWSS) of enterprises are considered. The kinetic equation for the activity concentration of the main sediment component – Ca2+ ions in circulating water (CW) is discussed. Based on this equation, expressions were obtained for the rate of formation of CaCO3 from CW and the stability index of CW, which is expressed by the activity concentration of free Ca2+ ions not bound in CaCO3. These values are determined by measuring parameters of the quality of CW and the mode of operation of the recirculating system, which are provided for by the regulations for the operation of the RWSS Current information on the value of the stability index makes it possible to calculate the rate of CaCO3 precipitation and, if necessary, to develop quantitative parameters of operational measures to stabilize CW. The algorithm for calculating the stability index was applied to the RWSS of one of the HPPs, where softening of the feed water and bypass softening of CW are used. The calculated value of the index adequately reflects changes in the stability of the CW during variations in the operation mode of the RWSS. The stability index was used to calculate the parameters of CW acidification, which ensure the desired level of its stability.